Synthesis, in vitro safety and antioxidant activity of new pyrrole hydrazones - Tzankova Diana; Vladimirova Stanislava; Aluani Denitsa; Yordanov Yordan; Peikova Lily; Georgieva Maya (Acta Pharmaceutica)
Six new N-pyrrolylhydrazide hydrazones were synthesized under micro synthesis conditions, assuring about 59–93 % yield, low harmful emissions and reagent economy. The structures of the new compounds were elucidated by melting points, TLC characteristics, IR, 1H and 13C NMR spectral data followed by MS data. The purity of the obtained compounds was proven by the corresponding elemental analyses. “Lipinski’s rule of five” parameters were applied for preliminary evaluation of the pharmacokinetic properties of the target molecules. The initial in vitro safety screening for cytotoxicity (on HepG2 cells) and hemocompatibility (hemolysis assay) showed good safety of the new compounds, where ethyl 5-(4-bromophenyl)-1-(1-(2-(4-hydroxy-3-methoxybenzylidene)-hydrazineyl)-1-oxo-3-phenylpropan-2-yl)-2-methyl-1H-pyr-role-3-carboxylate (4d) and ethyl 5-(4-bromophenyl)-1-(1-(2-(2-hydroxybenzylidene)hydrazineyl)-1-oxo-3-phenylpropan--2-yl)-2-methyl-1H-pyrrole-3-carboxylate (4a) were the least toxic. The antioxidant activity in terms of radical scavenging activity (DPPH test) and reducing ability (ABTS) was also evaluated. The antioxidant protective potential of the compounds was next determined in different in vitro cellular-based models, revealing compounds 4d and 3 [ethyl 5-(4-bromophenyl)-1-(1-hydrazineyl-1-oxo-3-phenylpropan-2-yl)-2-methyl-1H-pyrrole-3-carboxylate] as the most promising compounds, with 4d having better safety profile.